CORPORATE GOVERNANCE'S ROLE IN SHAPING TRANSFER PRICING PRACTICES - Clearesta Gianchiara; Arya Pradipta; Magda Siahaan (Transpublika Publisher, 2024)
This study aims to uncover evidence on the impact of tax, bonuses, company size, tunneling incentives, profitability, corporate governance, and sales growth on transfer pricing. This research is based on existing data and utilizes a selective sampling technique to gather data from 49 manufacturing firms listed on the Indonesia Stock Exchange between 2015 and 2020. The findings suggest that the size of a company and its corporate governance practices play a role in influencing transfer pricing. On the other hand, factors like taxes, bonuses, profit margins, and sales growth do not seem to impact transfer pricing decisions. The size of a company may impact management’s choices regarding transfer pricing activities with affiliated entities.